Language conflict and language rights: Ethnolinguistic perspectives on human conflict - Davies, William D. 1954-2017; Dubinsky, Stanley 1952- (Cambridge (UK): Cambridge University Press, 2018)
As the colonial hegemony of empire fades around the world, the role of language in ethnic conflict has become increasingly topical, as have issues concerning the right of speakers to choose and use their preferred language(s). Such rights are often asserted and defended in response to their being violated. The importance of understanding these events and issues, and their relationship to individual, ethnic, and national identity, is central to research and debate in a range of fields outside of, as well as within, linguistics. This book provides a clearly written introduction for linguists and non-specialists alike, presenting basic facts about the role of language in the formation of identity and the preservation of culture. It articulates and explores categories of conflict and language rights abuses through detailed presentation of illustrative case studies, and distills from these key cross-linguistic and cross-cultural generalizations.
Note continued: Cases: Hungarians in Slovakia, Hispanics in the Southwestern United States, Kurds in Turkey -- 12. Minorities of Migration -- Cases: Roma in Europe, Koreans in Japan, Puerto Ricans in the United States -- 13. Intra-Linguistic (Dialectal) Minorities -- Cases: Okinawans in Japan, African American English in the United States -- 14.Competition for Linguistic Dominance -- Cases: Flemish versus Walloons in Belgium, Tamils versus Sinhalese in Sri Lanka, French versus English in Canada -- Further Reading and Resources for Part III -- pt. IV Language Endangerment, Extinction, and Revival -- 15. Endangered Languages: Taxonomy, Ecology, and Ownership -- 16. Language Revitalization and Revival -- Cases: Welsh, Hebrew.
Includes bibliographical references and index.
Keywords: Linguistic change -- Social aspects; Group identity -- Social aspects; Ethnocentrism; Changement linguistique -- Aspect social; x; Ethnocentrisme; ethnocentrism; Ethnocentrism; Linguistic change -- Social aspects; Minderheitensprache; Sprachkonflikt; Sprachpolitik; Sprachwandel